HUBUNGAN ANTARA LAMA SIKLUS MENSTRUASI DAN KADAR TRIGLISERIDA PADA MAHASISWA PSKPS ULM - Hanifah, Medina; Huldani, Huldani; Biworo, Agung (Homeostasis, 2024)
Abstract: Triglyceride levels influenced by several things, one of which is the menstrual cycle, the length of the menstrual cycle is varied. The length of the menstrual cycle is influenced by the follicular phase, in the end follicular phase, the hormone estrogen increases compared to the hormone progesterone. Estrogen hormone can suppress lipoprotein lipase (LPL). This study aims to explain the relationship between the length of the menstrual cycle and triglyceride levels in ULM PSKPS students class of 2020-2022. This research was done with an analytical observational method with a cross sectional approach, using purposive sampling technique. Research subjects were asked to fill out a research question and answer sheet via google form. There were 32 PSKPS ULM students who met the inclusion and exclusion criteria and measured triglyceride levels. Data analysis used the Spearman correlation statistical test. The results of data analysis found that there was no significant relationship between the length of the menstrual cycle and triglyceride levels in ULM PSKPS students. (r = 0.035, p = 0.851) Keywords: length of menstrual cycle, triglyceride, Medical student of PSKPS ULM. Abstrak: Kadar trigliserida dipengaruhi oleh beberapa hal, salah satunya adalah siklus menstruasi, lamanya siklus menstruasi bervariasi. Lamanya siklus menstruasi dipengaruhi oleh fase folikuler, pada fase folikuler akhir, hormon estrogen meningkat dibandingkan hormon progesteron. Hormon estrogen dapat menekan lipoprotein lipase (LPL). Penelitian ini bertujuan untuk menjelaskan hubungan lama siklus menstruasi dengan kadar trigliserida pada mahasiswi PSKPS ULM angkatan 2020-2022. Penelitian ini dilakukan dengan metode observasional analitik dengan pendekatan cross sectional, menggunakan teknik purposive sampling. Subjek penelitian diminta untuk mengisi kuesioner dan lembar jawaban penelitian melalui google form. Terdapat 32 mahasiswa PSKPS ULM yang memenuhi kriteria inklusi dan eksklusi dan dilakukan pengukuran kadar trigliserida. Analisis data menggunakan uji statistik korelasi Spearman. Hasil analisis data menunjukkan bahwa tidak terdapat hubungan yang signifikan antara lama siklus menstruasi dengan kadar trigliserida pada mahasiswi PSKPS ULM. (r = 0.035, p = 0.851) Kata-kata kunci: lama siklus menstruasi, trigliserida, mahasiswa PSKPS ULM